Effects of Rituximab Including Long-term Maintenance Therapy in Children with Nephrotic Syndrome in a Single Center of Korea - Seong Heon Kim; Taek Jin Lim; Ji Yeon Song; Su Young Kim (Korean Society of Pediatric Nephrology, 2018)
Rituximab (RTX) is a chimeric monoclonal antibody that inhibits CD20-mediated B-cell proliferation and differentiation. Several studies have examined its use in intractable nephrotic syndrome (NS) with some positive results. However, those studies examined such effects for a short-term period of 1 year, and some patients continued to relapse after a lapse in RTX treatment. Our use of RTX as a maintenance therapy (RTX injection when the CD19 cell count exceeded 100-200/μL before relapse) showed some noticeable efficacy. We used RTX in 19 patients with steroid-dependent NS (SDNS). In 12 patients treated with RTX maintenance therapy, only one relapse occurred. The mean treatment period was 23.4±12.7 months, and the mean number of RTX administrations was 3.9±1.6. The relapse rates were decreased (from 2.68/year to 0.04/year), and the drug-free period also increased (from 22.5 days/year to 357.1 days/year) during maintenance therapy. The other seven patients were treated with one cycle of RTX or additional cycles in case of relapse (non-maintenance therapy). Relapse rates were significantly decreased after RTX treatment (from 1.76/year to 0.96/year, P=0.017). The relapse-free period was 15.55±7.38 (range, 5.3-30.7) months. No severe side effects of RTX were found except for a hypersensitivity reaction such as fever and chills during its infusion. In conclusion, RTX is considered an effective and safe option to reduce the relapse rate by a single- or maintenance-interval therapy in SDNS.